Identification of Respiratory Fungal Infections using Cytoscreening (Journal of Universal Science Research, 2024)
Cytoscreening is a simple and rapid technique that requires a high index of suspicion due to the increased reported cases worldwide  especially  among the  immunocompromised patients.  The  identification of fungal infection by cytoscreening depends on the finding of the causing agent or its effects (inflammatory cells and cytopathic effects). This study aimed to identify respiratory fungal infections using cytoscreening. Fifty-nine cytological smears were used in this study, 56 of which were sputum samples representing (95.2%) and 3 were BAL representing (4.8%). Samples were smeared directly on clean dry slide and stained by Grocott’s Hexamine Silver. Of the total sample size, there were 31 (52.5%) male samples and 28 (47.4%)female samples. The patients’ ages ranged between 20- 75 years old with mean of 45.19 years. The age interval 20-59 was 47 representing (79.7%) while the age interval more than 59 years was 12 representing (20.3%). Clinical distribution of patients revealed 31 (52.5%) asthmatic patients from which 12 (38. 7%) were male and 19 (67.8%) female, 15 patients with TB from which 12 (38.7%) were male and 3 (10.7%)female, 12 CF patients from which 7 (28.6%) were male and 5 (17.9%)female and one female cancer patient representing (3.6%) and absent of male. Yeast cells have been in 2 sample representing 3.6% and inflammatory background has been seen in 51 samples (86.4%) while 8 samples (13.6%) had no inflammatory background. The present study concluded that Grocott’sHexamine Silver stain is might help in identification of fungi and its inflammatory background.